PENERAPAN METODE PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 005 LENGGADAI HILIR - Ermawati '; Zetra Hainul Putra; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research carried out base on the lowly of the result of mathematic subject in 2nd grade SDN 005 Lenggadai Hilir which is about 55,25 within minimal completeness criterion stated is 65. The subject of this research is 2nd grade students of SDN 005 Lenggadai Hilir which is total of 20 students, consisted of 10 boys and 10 girls. This was a classroom action research which has two cycles which was conducted on March 23rd to April 2nd 2015. The purpose of this research is to improve student’s achievement on mathematics of the 2nd grade student SDN 005 Lenggadai Hilir with the application of inquiry learning method. Instruments for collecting data are teacher’ and students’ observation sheets and test. The data shown that either learning process or students’ achievement increased. This was seen from students’ and teacher’s scores in learning process increased. First cycle at the first meeting teacher’s activity was 66,66% categorized as enough and increased at the second meeting became 79,16% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of teacher’s activity increased as 83,33% categorized as good and at the second meeting it increased became 91,66% categorized as very good. While students activities in learning process also increased. At the first cycle at the first meeting students activities was 62,5% categorized as enough and increased at the second meeting became 75% categorized as good. Meanwhile at the second cycle at the first meeting the percentage of students activities increased as 79,16% categorized as good and at the second meeting it increased became 91,66% categorized as very good. The average of student’ achievement on basic score was 55,25, UH 1 was 64,5 and UH 2 was 78,75. From basic score to UH 1 incresed 16,74%, and from UH 1 to UH 2 increased again became 22,09%. However, the ending of daily examination was 85%. Based on the result it can be concluded that impementation learning through inquiry learning method increased learning process and students’ achievement on mathematic students 2nd grade of SDN 005 Lenggadai Hilir.Keywords: Inquiry Learning Methode, Learning Achievement on Mathematics